Christian Axboe Nielsen, Yugoslavia and Political Assassinations: The History and Legacy of Tito's Campaign Against the Émigrés (London; New York: I. B. Tauris, 2020), 253 str. (Časopis za suvremenu povijest, 2021)
Prikaz knjige